Liver X receptor modulators: a review of recently patented compounds (2009 – 2012). (October 2013) - Loren, Jon; Huang, Zhihong; Laffitte, Bryan A; Molteni, Valentina
<x xml:space="preserve">Abstract</x> Introduction: The development of small molecule agonists of the liver X receptors (LXRs) has been an area of interest for over a decade, given the critical role of those receptors in cholesterol metabolism, glucose homeostasis, inflammation, innate immunity and lipogenesis. Many potential indications have been characterized over time including atherosclerosis, diabetes, inflammation, Alzheimer's disease and cancer. However, concerns about the lipogenic effects of full LXRα/β agonists have required extensive efforts aimed at identifying LXRβ agonist with limited activity on the LXRα receptor to increase the safety margins. Areas covered: This review includes a summary of the LXR agonists that have reached the clinic and summarizes the patent applications for LXR modulators from September 2009 to December 2012 with emphasis on chemical matters, biological data associated with selected analogs and therapeutic indications. Expert opinion: As LXR agonists have the potential to be useful for many indications, the scientific community, despite setbacks due to on-target side effects, has maintained interest and devised strategies to overcome safety hurdles. While a clinical proof of concept still remains elusive, the recent advancement of compounds into the clinic highlights that acceptable safety margins in preclinical species have been achieved.